Self-selected motivational music on the performance and perceived exertion of runners - Clark, J. C.; Baghurst, T.; Redus, B. S. (The Journal of Strength and Conditioning Research, 2021)
Music is used by athletes and exercisers to improve performance outcomes, but it is less known whether its properties can enhance performance at maximal intensity. This study measured subjects' performance time, average heart rate, and rating of perceived exertion (RPE) on a 1.5-mile running trial when listening to self-selected motivational music vs. no music. Subjects were 17 runners (male = 8, female = 9) who completed 2, 1.5-mile time trials in a repeated-measures randomized crossover design. For the music trial, subjects were asked to select and listen to a motivational song, which was scored by the subject for its motivational quotient using the Brunel Music Rating Inventory-2. Subjects improved mean performance time by 10 seconds and increased average heart rate by 4.5 b·min-1 in the motivational music condition, but neither were significantly different (p = 0.09, 0.10). However, the music condition significantly lowered subjects' RPE by 0.5 points (p = 0.02). That motivational music improved performance time, although not significant, is noteworthy considering the significantly lower RPE reported. Therefore, ergogenic qualities of motivational music may elicit a greater performance from experienced runners while simultaneously lowering perception of effort when working at maximal intensity.